PENGARUH PERILAKU PEMBELIAN HEDONIC DAN ULTILITARIAN TERHADAP STORE LOYALTY DI MATAHARI DEPARTMENT STORE MAKASSAR - Sukardi Sukardi (Jurnal Bisnis dan Kewirausahaan, 2015)
This study aimed to test and analyze the influence of hedonic and ultilitarian buying behavior on Store Loyalty of Matahari Department Store in Makassar. This study used independent variables; they are: hedonic and ultilitarian buying behavior; and a dependent variable, consumer Store loyalty. This study is a survey research which is used for explanatory purpose or confirmatory, or is also called a study for hypothesis testing that is to explain the influence of variables or a causal relation between variables through a hypothesis testing. The data were obtained by spreading and collecting questionnaires, and then they were analyzed by using logistic regression modeling. From the discussion and the testing of hedonic and ultilitarian buying behavior on Store Loyalty of Matahari Department Store in Makassar, of the hypotheses that had significant influences were hedonic buying behavior to Store Loyalty of Matahari Department Store in Makassar. The hypothesis which did not have significant influence was ultilitarian buying behavior to Store Loyalty of Matahari Department Store in Makassar.